Pengaruh Minat Belajar dan Kedisiplinan Belajar Siswa Terhadap Hasil Belajar Matematika - Ela Faisah; Ella Padilah; Yuyun Elizabeth Patras (Universitas Pakuan, 2023)
THE INFLUENCE OF LEARNING INTEREST AND STUDENT LEARNING DISCIPLINES ON MATHEMATICS LEARNING RESULTSThe purpose of this study was to examine the effect of interest in learning (X1) on mathematics learning outcomes (Y), read the impact of student learning discipline (X2) on mathematics learning outcomes (Y), and investigate the effect of learning interest (X1) and learning discipline (X2) together on mathematics learning outcomes (Y). The research method used is quantitative with an ex post facto survey strategy. The sample size was 42 respondents selected by proportional random sampling technique from students of SD Negeri Ciseureuh and SD Negeri Loji Batulawang cluster, Cipanas sub-district, Cianjur district. This research will be implemented in the even semester of the 2021/2022 academic year. The instrument validity test uses the Person Product Moment correlation formula, and the reliability test uses the Cronbach Alpha formula. Test the data analysis requirements using normality and homogeneity tests. The results showed a positive and very significant relationship with a moderate strength of the relationship (r = 0.750 p 0.01) between the X1 variable and the Y variable. There was a positive and very significant relationship with a moderate relationship strength (r = 0.643 p 0 0.01) between variables X2 and variable Y. There is a positive and very significant relationship with moderate strength (r = 0.805 p 0.01) between variables X1 and X2 together with variable Y